Eosinophils Control Liver Damage by Modulating Immune Responses Against Fasciola hepatica - Frigerio, Sofía; da Costa, Valeria; Costa, Monique; Festari, María Florencia; Landeira, Mercedes; Rodríguez-Zraquia, Santiago A.; Härtel, Steffen; Toledo, Jorge; Freire, Teresa (Frontiers in Immunology, 2020)
Eosinophils are granulocytes that participate in the defense against helminth parasites and in hypersensitivity reactions. More recently, eosinophils were shown to have other immunomodulatory functions, such as tissue reparation, metabolism regulation and suppression of Th1 and Th17 immune responses. In the context of parasitic helminth infections, eosinophils have a controversial role, as they can be beneficial or detrimental for the host. In this work, we investigate the role of eosinophils in an experimental infection in mice with the trematode parasite Fasciola hepatica, which causes substantial economical losses around the world due to the infection of livestock. We demonstrate that eosinophils are recruited to the peritoneal cavity and liver from F. hepatica-infected mice and this recruitment is associated with increased levels of CCL11, TSLP and IL-5. Moreover, the characterization of peritoneal and hepatic eosinophils from F. hepatica-infected mice showed that they express distinctive molecules of activation and cell migration. Depletion of eosinophils with an anti-Siglec-F antibody provoked more severe clinical signs and increased liver damage than control animals which were accompanied by an increase in the production of IL-10 by hepatic and splenic CD4+ T cells. In addition, we also report that eosinophils participate in the modulation of humoral immune responses during F. hepatica infection, contributing to their degranulation. In conclusion, we demonstrate that eosinophils are beneficial for the host during F. hepatica infection, by limiting the production of IL-10 by specific CD4+ T cells and favoring eosinophil degranulation induced by specific antibodies. This work contributes to a better understanding of the role of eosinophils in parasitic helminth infections.